Intergenic long noncoding RNAs provide a novel layer of post-transcriptional regulation in development and disease - Tan, J (2014)
Recent genome-wide sequencing projects revealed the pervasive transcription of intergenic long noncoding RNAs (lincRNAs) in eukaryotic genomes (reviewed in Ponting et al. 2009). For the vast majority of lincRNAs, their mechanisms of function remain largely unrecognized. However, the genome-wide signatures of functionality associated with many lincRNAs, including apparent evolutionary sequence conservation, spatial and temporal-restricted expression patterns, strong associations with epigenetic marks, and reported molecular and cellular functions, reinforce their biological relevance. My work investigates lincRNAs that post-transcriptionally regulate gene abundance by competing for the binding of common microRNAs (miRNAs) with protein-coding transcripts, termed competitive endogenous RNAs (ceRNAs) acting lincRNAs (lnceRNAs). First, I examine the biological relevance of this post-transcriptional regulation of gene abundance by ceRNAs. Next, I estimate the genome-wide prevalence of lnceRNAs in mouse embryonic stem cells (mESCs) and characterize their properties. Finally, using two specific examples of lnceRNAs, I show the contributions of lnceRNAs to human monogenic and complex trait diseases. Collectively, these results illustrate that lnceRNAs provide a novel layer of post-transcriptional regulation via a miRNA-mediated mechanism that contributes to organismal and cellular biology.